1960
DOI: 10.1182/blood.v15.5.706.706
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Thrombocythemia: A Critical Review

Abstract: 707 conl)lying with the above definition, with the exception of a Ilumber in which tiit' thrombocythemia appeared to be a mere transient i ase in tile course of otiler well substantiated (liSeaSeS. A history of hemorrhage was essential for inclusioii. Either thrombocytosis or thrombosis without hemorrhage VdS illsufficient; for example, cases 1 and 2 reported by Fanger et al.'1' were included, while case 3 was excluded because the patient had not i)led. A diagnosis of "essential" or "idiopathic" thrombocythemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

1963
1963
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Our findings of incidences around 50% represent almost a median of previous reported results. The IT group in the present study, showing increased NAP scores in 25% of the cases, is very small and no other reports, except 2 cases with very high NAP scores reported by Gum (17), are available for comparison. We have been able to show a statistically significant difference in the incidences of decreased and increased NAP scores between CML and the other representatives of the myeloproliferative syndrome (p(O.001).…”
Section: Single Cell N a P Activity;contrasting
confidence: 61%
“…Our findings of incidences around 50% represent almost a median of previous reported results. The IT group in the present study, showing increased NAP scores in 25% of the cases, is very small and no other reports, except 2 cases with very high NAP scores reported by Gum (17), are available for comparison. We have been able to show a statistically significant difference in the incidences of decreased and increased NAP scores between CML and the other representatives of the myeloproliferative syndrome (p(O.001).…”
Section: Single Cell N a P Activity;contrasting
confidence: 61%
“…Note clusters of megakaryocytes (arrows) and atypical forms. Hematoxylin and eosin stain; original magnification x 100; reduced by 25 percent.karyocytic preponderance and increased reticulin deposition (FIGS 3. and 4).A bone marrow aspirate and biopsy from the iliac crest confirmed the initial impression of a myeloproliferative disease.…”
mentioning
confidence: 88%
“…With busulfan, most patients also reached CR, and remained in CR for a prolonged period after the drug was discontinued. The efficacy of busulfan3 or other alkylating drugs, such as No. 3 ESSENTIAL THROMBOCYTHEMIA -Fenazu et al 555 melphalan, chlorambucil, or lomustine (CCNU),I5 has also been shown in ET.…”
Section: Vol 66mentioning
confidence: 99%